Gut Virome: Role and Distribution in Health and Gastrointestinal Diseases - Spencer, Laurie; Olawuni, Babatunde; Singh, Pallavi (Frontiers in Cellular and Infection Microbiology, 2022)
The study of the intestinal microbiome is an evolving field of research that includes comprehensive analysis of the vast array of microbes – bacterial, archaeal, fungal, and viral. Various gastrointestinal (GI) diseases, such as Crohn’s disease and ulcerative colitis, have been associated with instability of the gut microbiota. Many studies have focused on importance of bacterial communities with relation to health and disease in humans. The role of viruses, specifically bacteriophages, have recently begin to emerge and have profound impact on the host. Here, we comprehensively review the importance of viruses in GI diseases and summarize their influence in the complex intestinal environment, including their biochemical and genetic activities. We also discuss the distribution of the gut virome as it relates with treatment and immunological advantages. In conclusion, we suggest the need for further studies on this critical component of the intestinal microbiome to decipher the role of the gut virome in human health and disease.